A SiO2 coated structural material and its preparation method and application
By encapsulating the SiO2-clad structural material of metal oxide nanoclusters inside the SiO2 nanospheres, the problem of sintering of supported metal catalysts at high temperatures is solved, the high dispersion and reaction activity of the catalyst are achieved, and the butene production reaction is improved efficiency.
Patent Information
- Application Number
- CN202411562226.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Supported metal catalysts are prone to sintering under high temperature reaction conditions, resulting in reduced dispersion of active sites and deactivation of catalysts.
Using SiO2 coated structural material, a stable and uniform dispersion system is constructed by encapsulating metal oxide nanoclusters inside SiO2 nanospheres, including Cu and metal elements such as Zr, Yb, Hf, Y, Zn, etc., using the reverse microemulsion method. Avoid high temperature sintering.
The catalyst's anti-sintering ability is improved, the high dispersion and reaction activity of metal active sites are maintained, and the ethanol conversion rate and butene selectivity in the one-step butene process of ethanol production is significantly improved.
Smart Images

Figure CN119076066B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a SiO2 coated structural material and a preparation method and application thereof. Background Art
[0002] Cu has a low Tammann temperature and is prone to agglomeration and deactivation under high-temperature reaction conditions. Migration-coalescence and Ostwald ripening are two mechanisms that cause the agglomeration and sintering of metal nanoparticles, and migration-coalescence is very likely to occur in high-temperature processes. Therefore, this severe challenge faced by Cu-based catalysts has prompted researchers to continuously develop new strategies to stabilize metal active sites. Currently, supported metal catalysts are widely used due to their sufficient active sites and high atomic utilization.
[0003] However, supported metal catalysts are prone to high-temperature sintering in a reducing gas environment (such as H2). Sintering significantly reduces the dispersion of active sites of supported catalysts, causing a sharp decrease in the number of active sites exposed by the catalyst, which in turn leads to low catalyst activity. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a SiO2 coated structural material and its preparation method and application. The SiO2 coated structural material provided by the present invention has strong anti-sintering ability; it is used as a catalyst for catalyzing the one-step ethanol to butene reaction, and has high ethanol conversion rate and butene selectivity.
[0005] In order to achieve the above object, the present invention provides the following scheme:
[0006] The invention provides a SiO2 coated structural material, comprising SiO2 nanospheres and metal oxide nanoclusters encapsulated inside the SiO2 nanospheres; the metal elements of the metal oxide nanoclusters include Cu and at least one of Zr, Yb, Hf, Y and Zn.
[0007] Preferably, the diameter of the SiO2 nanospheres is 20-30 nm.
[0008] Preferably, the molar ratio of the metal oxide nanoclusters to SiO2 is (0-2.18):(3.29-52.23), and the molar number of the metal oxide nanoclusters is not zero.
[0009] The present invention provides a method for preparing the SiO2 coated structural material described in the above scheme, comprising the following steps:
[0010] An alkane organic solvent, a surfactant, ammonia water, an acetylacetonate metal salt and a silicon source are mixed, and the mixture is hydrolyzed and polycondensed, and the solid-liquid separation is performed to obtain a SiO2-coated acetylacetonate metal salt material; the acetylacetonate metal salt comprises copper acetylacetonate, and at least one of zirconium acetylacetonate, ytterbium acetylacetonate, hafnium acetylacetonate, yttrium acetylacetonate and zinc acetylacetonate;
[0011] The SiO2 coated acetylacetonate metal salt material is calcined to obtain the SiO2 coated structural material.
[0012] Preferably, the molar ratio of the copper acetylacetonate to the metal salt of acetylacetonate other than copper acetylacetonate is (0-0.9):(0-1.28), and both are not 0.
[0013] Preferably, the silicon source includes tetramethoxysilane and octadecyltrimethoxysilane.
[0014] Preferably, the molar ratio of the acetylacetonate metal salt to the silicon source is (0-2.18):(3.29-52.23), and the molar number of the acetylacetonate metal salt is not 0.
[0015] Preferably, the calcination temperature is 600-800° C., and the holding time is 2-6 hours.
[0016] Preferably, the calcination atmosphere is air atmosphere.
[0017] The present invention provides the use of the SiO2 coated structural material described in the above scheme or the SiO2 coated structural material prepared by the preparation method described in the above scheme as a catalyst in catalyzing the one-step production of butene from ethanol.
[0018] The present invention provides a SiO2 coated structural material, comprising SiO2 nanospheres and metal oxide nanoclusters encapsulated inside the SiO2 nanospheres; the metal elements of the metal oxide nanoclusters include Cu and at least one of Zr, Yb, Hf, Y and Zn. The SiO2 coated structural material of the present invention encapsulates the metal oxide nanoclusters in SiO2 (confinement effect), so high-temperature sintering is not easy to occur, thereby avoiding catalyst deactivation.
[0019] The present invention breaks the fixed idea of coating metal nanoparticles or oxides, but directly coats organic metal salts (acetylacetonate metal salts) to synthesize SiO2 coated organic metal salt precursors. Compared with the existing SiO2 coating technology, the method provided by the present invention overcomes the two-step traditional process of first preparing the coating center and then encapsulating, and only uses a one-step process to achieve coating.
[0020] The present invention utilizes the characteristics of organic metal salts being uniformly dispersed and not easily dissolved in low-temperature organic solvents for coating, thereby avoiding the defect that inorganic metal salts cannot be dispersed in organic solvents. The present invention adopts the reverse microemulsion method to construct a stable and uniform dispersion system, and can accurately control the particle size of SiO2 nanospheres (by controlling the concentration of ammonia water and the amount of silicon source added to control the particle size of SiO2 nanospheres), limit the nucleation, growth and agglomeration process of nanoparticles, and thus achieve uniform dispersion of organic metal salts in SiO2 nanospheres.
[0021] The invention decomposes the acetylacetone metal salt into metal oxides by calcination and can further improve the metal dispersion. Compared with the traditional coating and impregnation method, the invention can synthesize the SiO2 coated anti-sintering catalyst in situ.
[0022] The method provided by the present invention has universal applicability and can synthesize highly dispersed catalysts of corresponding metals by changing the type of coated organic metal salts. Compared with traditional coating methods, the method has a wider application range.
[0023] Compared with the currently advanced technology for producing jet fuel from alcohol, the present invention produces butene from ethanol in one step, thereby eliminating the ethylene oligomerization step, reducing the amount of unit operations, and thus saving energy consumption.
[0024] Compared with traditional supported metal catalysts, the catalyst synthesized by this method has higher ethanol conversion rate and butene selectivity in the one-step ethanol to butene reaction, which is due to the good sintering resistance of Cu and Lewis acid site Zr, Yb, Hf, Y and Zn species. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0026] Figure 1 Cu obtained in Example 5 of the present invention 16 X-ray diffraction (XRD) of Zr@SiO2 and the sample after reaction; the abscissa 2θ of the XRD spectrum is the diffraction angle, and the ordinate I is the diffraction intensity;
[0027] Figure 2 Cu obtained in Example 5 of the present invention 16 Transmission Electron Microscope (TEM) of Zr@SiO2;
[0028] Figure 3 Cu obtained in Example 5 of the present invention 16 Line scan of Zr@SiO2; in the right figure, the horizontal axis D is the selected sample linear position, and the vertical axis I represents the intensity;
[0029] Figure 4 Cu obtained in Example 5 of the present invention 16 H2-TPR (Temperature Program Reduction) diagram of Zr@SiO2; the horizontal axis T in the H2-TPR diagram is the temperature, and the vertical axis A is the H2 consumption;
[0030] Figure 5 For the traditional supported catalyst Cu 16 / Zr / SiO2 and XRD patterns of the samples after reaction; the abscissa 2θ of the XRD spectrum is the diffraction angle, and the ordinate I is the diffraction intensity;
[0031] Figure 6 For the traditional supported catalyst Cu 16 H2-TPR diagram of / Zr / SiO2; the abscissa T of H2-TPR is temperature, and the ordinate A is H2 consumption;
[0032] Figure 7 For the traditional supported catalyst Cu 16 TEM image of / Zr / SiO2;
[0033] Figure 8 For the traditional supported catalyst Cu 16 / Zr / SiO2 and Cu obtained in Example 5 of the present invention 16 Schematic diagram of anti-sintering of Zr@SiO2. DETAILED DESCRIPTION
[0034] The present invention provides a SiO2 coated structural material, comprising SiO2 nanospheres and metal oxide nanoclusters encapsulated inside the SiO2 nanospheres; the metal elements in the metal oxide nanoclusters include Cu and at least one of Zr, Yb, Hf, Y and Zn.
[0035] In the present invention, the molar ratio of Cu to metals other than Cu is preferably (0-0.9): (0-1.28), and neither is 0, further preferably (0.05-0.80): (0.1-1.1), and more preferably (0.12-0.50): (0.2-0.8). In an embodiment of the present invention, the metals in the metal oxide nanocluster core are Cu and Yb, and the molar ratio of Cu and Yb is 0.16:0.64; or Cu and Hf, and the molar ratio of Cu and Hf is 0.16:0.64; or Cu and Y, and the molar ratio of Cu and Y is 0.16:0.64; or Cu and Zn, and the molar ratio of Cu and Zn is 0.16:0.64; or Cu and Zr, and the molar ratio of Cu and Zr is (0-0.9): (0-1.28), and neither is 0.
[0036] In the present invention, the diameter of the SiO2 nanosphere is preferably 20-30 nm, and more preferably 22-28 nm. In the present invention, the molar ratio of the metal oxide nanocluster to SiO2 is preferably (0-2.18): (3.29-52.23), and the molar number of the metal oxide nanocluster is not 0.
[0037] The present invention provides a method for preparing the SiO2 coated structural material described in the above scheme, comprising the following steps:
[0038] An alkane organic solvent, a surfactant, ammonia water, an acetylacetonate metal salt and a silicon source are mixed, and the mixture is hydrolyzed and polycondensed, and a SiO2 layer is coated on the surface of the acetylacetonate metal salt, and solid-liquid separation is performed to obtain a SiO2-coated acetylacetonate metal salt material; the acetylacetonate metal salt comprises copper acetylacetonate, and at least one of zirconium acetylacetonate, ytterbium acetylacetonate, hafnium acetylacetonate, yttrium acetylacetonate and zinc acetylacetonate;
[0039] The SiO2 coated acetylacetonate metal salt material is calcined to obtain the SiO2 coated structural material.
[0040] Unless otherwise specified, the materials and equipment used in the present invention are commercially available.
[0041] The invention mixes an alkane organic solvent, a surfactant, ammonia water, acetylacetone metal salt and a silicon source, performs hydrolysis and polycondensation, coats a SiO2 layer on the surface of the acetylacetone metal salt, separates the solid from the liquid, and obtains a SiO2-coated acetylacetone metal salt material.
[0042] In the present invention, the mixing of the alkane organic solvent, the surfactant, aqueous ammonia, the acetylacetone metal salt and the silicon source preferably comprises the following steps:
[0043] Mixing a first alkane organic solvent, a surfactant and aqueous ammonia to obtain a mixed solution 1;
[0044] Mixing a second alkane organic solvent, acetylacetone metal salt and a silicon source to obtain a second mixed solution;
[0045] The mixed solution 1 and the mixed solution 2 are mixed.
[0046] In the present invention, the first alkane organic solvent and the second alkane organic solvent are preferably cyclohexane; the surfactant preferably includes polyoxyethylene nonylphenyl ether. In the present invention, the molar ratio of the first alkane organic solvent to ammonia water is preferably (230.41-921.64): (13.35-53.42), and more preferably (300-800): (20-45). The molar amount of ammonia water in the present invention refers to the molar amount of NH3•H20 in ammonia water.
[0047] In the present invention, the volume ratio of the ammonia water to the surfactant is preferably (1-4): (10-20), and more preferably (1.5-3.3): (12-16); the mass concentration of the ammonia water is preferably 25%. In the present invention, the surfactant has an emulsifying effect.
[0048] In the present invention, the temperature of the first mixing is preferably 20°C to 30°C, and more preferably 22°C to 28°C.
[0049] In the present invention, under the action of ammonia water, the coated structural material is obtained after nucleation, coalescence, agglomeration and heat treatment in microbubbles. In the present invention, ammonia water has two main functions. One is to adjust the type of microemulsion. By adjusting the concentration of ammonia water, the W / O (oil-in-water) or O / W (water-in-oil) type of the microemulsion can be controlled. The second is to control the surface morphology and particle size of nanoparticles (referring to SiO2 coated structural materials): In the process of preparing the material, the concentration of ammonia water plays a role in controlling the surface morphology of nanoparticles. At a higher concentration of ammonia water, a larger particle size and a narrower particle size distribution can be obtained. Specifically, in the present invention, the mass concentration of ammonia water is controlled at 25%, and the diameter of SiO2 nanospheres can be controlled to be 20~30nm.
[0050] In the present invention, the acetylacetonate metal salt includes copper acetylacetonate and at least one of zirconium acetylacetonate, ytterbium acetylacetonate, hafnium acetylacetonate, yttrium acetylacetonate and zinc acetylacetonate; the molar ratio of the copper acetylacetonate to the acetylacetonate metal salt other than copper acetylacetonate is preferably (0-0.9): (0-1.28), and both are not 0, and more preferably (0.05-0.80): (0.1-1.1).
[0051] In the present invention, the silicon source preferably includes tetramethoxysilane (TMOS) and octadecyltrimethoxysilane (C 18 TMS). The molar ratio of tetramethoxysilane to octadecyltrimethoxysilane is preferably (3.29-39.51): (0-12.72), and the molar number of octadecyltrimethoxysilane is not 0, and is more preferably (3-39): (0.1-12).
[0052] In the present invention, the molar ratio of the acetylacetone metal salt to ammonia water is preferably (0-2.18):(13.35-53.42). The molar amount of ammonia water in the present invention refers to the molar amount of NH3•H20 in ammonia water.
[0053] In the present invention, the molar ratio of the acetylacetone metal salt to the silicon source is preferably (0-2.18): (3.29-52.23), and the acetylacetone metal salt is not 0, and is further preferably (0.15-1.9): (3.3-51), and is more preferably (0.32-1.3): (6-30). The molar ratio of the second alkane organic solvent to the acetylacetone metal salt is preferably (230.41-921.64): (0-2.18), and the molar amount of the acetylacetone metal salt is not 0, and is further preferably (300-800): (0.15-1.9), and is more preferably (350-700): (0.32-1.3).
[0054] In the present invention, the temperature of the hydrolysis and polycondensation is preferably 20-40°C, more preferably 25-35°C; the time of the hydrolysis and polycondensation is preferably 1 hour. In the present invention, the hydrolysis and polycondensation are preferably carried out under stirring.
[0055] In the present invention, the solid-liquid separation preferably comprises centrifugation.
[0056] After completing the solid-liquid separation, the present invention preferably washes and dries the obtained solid.
[0057] In the present invention, the washing is preferably performed twice with ethanol; the drying temperature is preferably 40-120°C, more preferably 50-100°C, and more preferably 60-90°C; the drying time is preferably 10-20h, more preferably 12-18h, and more preferably 14-16h.
[0058] After obtaining the SiO2 coated acetylacetonate metal salt material, the present invention calcines the SiO2 coated acetylacetonate metal salt material to obtain the SiO2 coated structural material.
[0059] In the present invention, the calcination temperature is preferably 600-800°C, more preferably 620-780°C, and more preferably 630-700°C; the calcination holding time is preferably 2-6h, more preferably 2.5-5.5h, and more preferably 3-5h; the calcination atmosphere is preferably air atmosphere. In the present invention, the calcination temperature is preferably increased from 25°C to the calcination temperature, and the heating rate is preferably 2°C / min.
[0060] In the calcination process of the present invention, the acetylacetonate metal salt is decomposed into metal oxides and can be further dispersed.
[0061] The present invention provides the use of the SiO2 coated structural material described in the above scheme or the SiO2 coated structural material prepared by the preparation method described in the above scheme as a catalyst in catalyzing the one-step production of butene from ethanol.
[0062] In the present invention, before the application, it is also preferred to sequentially granulate, dry and reduce pretreatment the SiO2 coated structural material. In the present invention, the particle size of the granulation is preferably 90~180μm, and more preferably 100~150μm. In the present invention, the drying preferably includes: loading the SiO2 coated structural material in a quartz tube reactor, heating to 400℃ at a rate of 5℃ / min in a He atmosphere of 10~100mL / min and maintaining for 0.5~8h. The present invention can remove moisture by drying. In the present invention, the atmosphere of the reduction pretreatment is preferably a hydrogen atmosphere. The flow rate of the hydrogen atmosphere is preferably 15~50mL / min, and more preferably 15~40mL / min. In the present invention, the temperature of the reduction pretreatment is preferably 300~370℃, and the time is preferably 0.5h. The present invention activates the active sites in the SiO2 coated structural material by reduction pretreatment.
[0063] In the present invention, the reaction temperature of the catalytic ethanol to butene is preferably 300-450°C, more preferably 350-410°C, and the weight hourly space velocity is preferably 0.3h -1 .
[0064] In the present invention, the SiO2 coated structural material is used as a catalyst to catalyze ethanol to butene in a fixed bed having a tubular quartz reactor at normal pressure, the catalyst bed temperature is measured by a K-type thermocouple, and the gas flow rate is controlled by a mass flow controller.
[0065] Specifically, ethanol (C2H5OH,>99%) was fed through a bubbler, a stainless steel line was heated to 150°C using a heating tape, and the H2 flow rate through the bubbler was changed to change the weight hourly space velocity (WHSV). The product was analyzed using an online gas chromatograph (Agilent 8860) equipped with a flame ionization detector and a thermal conductivity detector. Ethanol conversion, product selectivity, and WHSV were calculated as shown in Formula 1.
[0066] ; ;
[0067] Formula 1;
[0068] In formula 1, X (%) is the ethanol conversion rate; n u (mol) is the number of moles of carbon in the unreacted ethanol; n t (mol) is the mole of carbon in the total ethanol feed; S i (%) is the selectivity of product i; n i (%) is the molar number of carbon in product i; ∑ i n i (mol) is the mole number of all product carbons; WHSV is the weight hourly space velocity; V ethanol (mL·h −1 ) is the volume flow rate of ethanol; ρ ethanol (g·mL -1 ) is the density of ethanol; m c (g) is the mass of the catalyst.
[0069] In order to further illustrate the present invention, a SiO2 coated structural material provided by the present invention and its preparation method and application are described in detail below in combination with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0070] Example 1
[0071] Cu 16 The preparation method of Yb@SiO2 coated structural material is as follows: 460.82mmol cyclohexane, 16.89g polyoxyethylene nonylphenyl ether surfactant (16mL, density 1.056g / mL) and 26.71mmol ammonia water (2mL, mass concentration 25%) are added into a flask. Then, 0.64mmol ytterbium acetylacetonate and 0.16mmol copper acetylacetonate, 13.17mmol TMOS and 4.24mmol C dispersed in 460.82mmol cyclohexane are added into the mixed solution. 18TMS, stirred for 1 hour for hydrolysis and polycondensation, a SiO2 layer was coated on the surface of the acetylacetonate metal salt (ytterbium acetylacetonate and copper acetylacetonate), and the obtained solid was washed with ethanol after centrifugation, and then dried in a drying oven at 80°C for 10 hours to obtain a solid powder, i.e., the acetylacetonate metal salt-SiO2 composite material;
[0072] The acetylacetone metal salt-SiO2 composite material was placed in a muffle furnace, heated to 650°C at a rate of 2°C / min and calcined for 4 h to obtain the SiO2 coated structural material, denoted as Cu 16 Yb@SiO2.
[0073] Application Example 1
[0074] Cu 16 Yb@SiO2 coated structural materials are used as catalysts to catalyze the one-step production of butene from ethanol:
[0075] Cu 16 Yb@SiO2 was granulated to a particle size of 90~180μm, and then 0.15g of Cu 16 Yb@SiO2 was loaded in a quartz tube reactor and heated to 400 °C at a rate of 5 °C / min in a 20 mL / min He atmosphere and maintained for 1 h to remove moisture.
[0076] Before evaluating the catalytic performance, the catalyst was pretreated for reduction at 350°C by passing 20 mL / min of H2 for 0.5 h, and then the activity of ethanol one-step preparation of butene was evaluated: it was carried out at normal pressure in a fixed bed with a tubular quartz reactor (i.e., a quartz tube reactor), the catalyst bed temperature was measured with a K-type thermocouple, and the gas flow rate was controlled by a mass flow controller. Ethanol (C2H5OH, >99%) was fed through a bubbler, the stainless steel line was heated to 150°C using a heating tape, and the H2 flow rate through the bubbler was changed to change the weight hourly space velocity (WHSV).
[0077] The products were analyzed using an online gas chromatograph (Agilent 8860) equipped with a flame ionization detector and a thermal conductivity detector. The results are shown in Table 1.
[0078] Table 1 Cu 16 One-step preparation of butene from ethanol using Yb@SiO2
[0079]
[0080] One-step process of ethanol to butene: reaction temperature: 400℃, WHSV: 0.3h -1 .
[0081] Example 2
[0082] The preparation steps are the same as those in Example 1, except that ytterbium acetylacetonate is replaced by hafnium acetylacetonate. The obtained SiO2 coated structural material is denoted as Cu 16 Hf@SiO2.
[0083] Application Example 2
[0084] Cu 16 Hf@SiO2 coated structural material as catalyst for catalytic one-step preparation of butene from ethanol: The evaluation procedure is the same as that of Application Example 1. The product was analyzed using an online gas chromatograph (Agilent 8860) equipped with a flame ionization detector and a thermal conductivity detector, and the results are shown in Table 2.
[0085] Table 2 Cu 16 One-step preparation of butene from ethanol using Hf@SiO2
[0086]
[0087] One-step process of ethanol to butene: reaction temperature: 400℃, WHSV: 0.3h -1 .
[0088] Example 3
[0089] The preparation steps are the same as those in Example 1, except that ytterbium acetylacetonate is replaced by yttrium acetylacetonate. The obtained SiO2 coated structural material is denoted as Cu 16 Y@SiO2.
[0090] Application Example 3
[0091] Cu 16 Y@SiO2 coated structural material as catalyst for catalytic one-step preparation of butene from ethanol: The evaluation procedure is the same as that of Application Example 1. The product was analyzed using an online gas chromatograph (Agilent 8860) equipped with a flame ionization detector and a thermal conductivity detector, and the results are shown in Table 3.
[0092] Table 3 Cu 16 Y@SiO2 one-step preparation of butene from ethanol
[0093]
[0094] One-step process of ethanol to butene: reaction temperature: 400℃, WHSV: 0.3h -1 .
[0095] Example 4
[0096] The preparation steps are the same as those in Example 1, except that ytterbium acetylacetonate is replaced by zinc acetylacetonate. The obtained SiO2 coated structural material is denoted as Cu16 Zn@SiO2.
[0097] Application Example 4
[0098] Cu 16 Zn@SiO2 coated structural material as catalyst for catalytic one-step preparation of butene from ethanol: The evaluation procedure is the same as that of Application Example 1. The product was analyzed using an online gas chromatograph (Agilent 8860) equipped with a flame ionization detector and a thermal conductivity detector, and the results are shown in Table 4.
[0099] Table 4 Cu 16 One-step preparation of butene from ethanol using Zn@SiO2
[0100]
[0101] One-step process of ethanol to butene: reaction temperature: 400℃, WHSV: 0.3h -1 .
[0102] Example 5
[0103] The preparation steps are the same as those in Example 1, except that ytterbium acetylacetonate is replaced by zirconium acetylacetonate to obtain the SiO2 coated structural material, denoted as Cu 16 Zr@SiO2.
[0104] Application Example 5
[0105] Cu 16 Zr@SiO2 coated structural material as catalyst for catalytic one-step preparation of butene from ethanol: The evaluation procedure is the same as that of Application Example 1. The product was analyzed using an online gas chromatograph (Agilent 8860) equipped with a flame ionization detector and a thermal conductivity detector.
[0106] Table 5 Cu 16 One-step preparation of butene from ethanol using Zr@SiO2
[0107]
[0108] One-step process of ethanol to butene: reaction temperature: 400℃, WHSV: 0.3h -1 .
[0109] Example 6
[0110] The preparation steps are the same as those in Example 1, except that the added acetylacetonate metal salts are 0.64 mmol of zirconium acetylacetonate and 0.08 mmol of copper acetylacetonate, to obtain the SiO2 coated structural material, which is recorded as Cu8Zr@SiO2.
[0111] Application Example 6
[0112] The Cu8Zr@SiO2 coated structural material was used as a catalyst to catalyze the one-step preparation of butene from ethanol: the evaluation procedure was the same as that of Application Example 1. The product was analyzed using an online gas chromatograph (Agilent 8860) equipped with a flame ionization detector and a thermal conductivity detector, and the results are shown in Table 6.
[0113] Table 6 Activity of Cu8Zr@SiO2 in one-step ethanol-to-butene process
[0114]
[0115] One-step process of ethanol to butene: reaction temperature: 400℃, WHSV: 0.3h -1 .
[0116] Example 7
[0117] The preparation steps are the same as those in Example 1, except that the added acetylacetonate metal salt is 0.64 mmol of zirconium acetylacetonate and 0.32 mmol of copper acetylacetonate, to obtain the SiO2 coated structural material, denoted as Cu 32 Zr@SiO2.
[0118] Application Example 7
[0119] Cu 32 Zr@SiO2 coated structural material as catalyst for catalytic one-step preparation of butene from ethanol: The evaluation procedure is the same as that of Application Example 1. The product was analyzed using an online gas chromatograph (Agilent 8860) equipped with a flame ionization detector and a thermal conductivity detector.
[0120] Table 7 Cu 32 One-step preparation of butene from ethanol using Zr@SiO2
[0121]
[0122] One-step process of ethanol to butene: reaction temperature: 400℃, WHSV: 0.3h -1 .
[0123] Comparative Example 1
[0124] The supported catalyst Cu was prepared by conventional impregnation method. 16 / Zr / SiO2: 460.82mmol cyclohexane, 16.89g polyoxyethylene nonylphenyl ether surfactant and 26.71mmol ammonia water (2mL, mass concentration 25%) were added to the flask. Then, 13.17mmol TMOS and 4.24mmol C 18TMS, stirred for 1 hour, centrifuged and the obtained solid was washed with ethanol, and then dried in a drying oven at 80°C for 10 hours. Finally, the obtained solid powder was placed in a muffle furnace, heated to 650°C at a rate of 2°C / min and calcined for 4 hours. The obtained product was recorded as SiO2. Take 0.018 mol of SiO2, 0.64 mmol of zirconium acetylacetonate and 0.16 mmol of copper acetylacetonate, use water as solvent, and use the equal volume impregnation method to synthesize the solid product, which was dried in a drying oven at 80°C for 10 hours.
[0125] Finally, the obtained solid powder was placed in a muffle furnace and heated to 650 °C at a rate of 2 °C / min for 4 h. The obtained product was recorded as Cu 16 / Zr / SiO2.
[0126] Application Comparative Example 1
[0127] Cu 16 / Zr / SiO2 catalyst is used to catalyze the one-step preparation of butene from ethanol: The evaluation procedure is the same as that of Application Example 1. The product was analyzed using an online gas chromatograph (Agilent 8860) equipped with a flame ionization detector and a thermal conductivity detector, and the results are shown in Table 8.
[0128] Table 8 Cu 16 / Zr / SiO2 one-step preparation of butene from ethanol
[0129]
[0130] One-step process of ethanol to butene: reaction temperature: 400℃, WHSV: 0.3h -1 .
[0131] With Cu 16 Compared with Cu / Zr / SiO2, 16 The conversion rate of ethanol and butene selectivity of Zr@SiO2 in the one-step process of ethanol to butene were greatly improved.
[0132] Comparative Example 2
[0133] The preparation steps are the same as those in Example 5, except that copper acetylacetonate is not added, and the obtained product is recorded as Zr@SiO2.
[0134] Application Comparative Example 2
[0135] The Zr@SiO2 coated structural material was used as a catalyst to catalyze the one-step preparation of butene from ethanol: the evaluation procedure was the same as that of Application Example 1. The product was analyzed using an online gas chromatograph (Agilent 8860) equipped with a flame ionization detector and a thermal conductivity detector, and the results are shown in Table 9.
[0136] Table 9 Activity of Zr@SiO2 in one-step process for preparing butene from ethanol
[0137]
[0138] One-step process of ethanol to butene: reaction temperature: 400℃, WHSV: 0.3h -1 .
[0139] The main product of the one-step process of Zr@SiO2 ethanol to butene is ethylene, which indicates that the introduction of only Zr species is beneficial to the dehydration of ethanol but not conducive to the selective production of butene.
[0140] Comparative Example 3
[0141] The preparation steps are the same as those in Example 7, except that zirconium acetylacetonate is not added. The obtained product is recorded as Cu 32 @SiO2.
[0142] Application Comparative Example 3
[0143] Cu 32 @SiO2 coated structural material as catalyst for catalytic one-step preparation of butene from ethanol: The evaluation procedure is the same as that of Application Example 1. The product was analyzed using an online gas chromatograph (Agilent 8860) equipped with a flame ionization detector and a thermal conductivity detector, and the results are shown in Table 10.
[0144] Table 10 Cu 32 @SiO2 ethanol one-step preparation of butene activity
[0145]
[0146] Reaction temperature: 400℃, WHSV: 0.3h -1 .
[0147] Cu 16 @SiO2 The product of the one-step process of ethanol to butene is basically only acetaldehyde, which means that only the introduction of Cu species is beneficial to the dehydrogenation of ethanol and cannot produce butene, which further confirms the necessity of introducing Cu and Zr species.
[0148] Performance Testing
[0149] Figure 1 Cu obtained in Example 5 of the present invention 16 X-ray diffraction patterns of Zr@SiO2 and the samples after reaction. Figure 1 It can be seen that Cu 16The XRD patterns of Zr@SiO2 and the samples after the reaction have no Cu and Zr related peaks (referring to the metal oxide related peaks; in addition, since the nanometer size of the metal oxide nanoclusters obtained in the present invention is too small, the XRD pattern cannot detect the peaks of the metal oxide, only the characteristic peaks of amorphous SiO2, which further indicates that the Cu obtained in the present invention 16 Zr@SiO2 has strong sintering resistance.
[0150] Figure 2 Cu obtained in Example 5 of the present invention 16 Transmission electron microscopy image of Zr@SiO2. Cu 16 The electron microscope image of Zr@SiO2 shows that the catalyst is a well-dispersed SiO2 sphere with a diameter of 20~30nm (i.e., SiO2-coated structural material).
[0151] Figure 3 Cu obtained in Example 5 of the present invention 16 Line scan of Zr@SiO2. The results show that Cu 16 Zr@SiO2 is a SiO2-coated nanocluster structure material. Cu and Zr species are evenly dispersed inside the SiO2 sphere with a diameter of 30nm.
[0152] Figure 4 Cu obtained in Example 5 of the present invention 16 H2-programmed temperature reduction diagram of Zr@SiO2. The peak at 263°C corresponds to the reduction peak of Cu nanoclusters that have a weak interaction with SiO2. The peak at 388°C corresponds to the reduction peak of Cu that is difficult to reduce to metallic copper species, which may be related to the strong interaction between Cu and Zr species, indicating that some copper species may be distributed in a single atomic state. Figure 6 The comparison shows that the in-situ synthesis of SiO2-coated anti-sintering catalyst Cu by reverse microemulsion method 16 The interaction between Cu and support in Zr@SiO2 is better than that in Cu prepared by traditional impregnation method. 16 The interaction between Cu and the support in / Zr / SiO2 is strong.
[0153] Figure 5 For the traditional supported catalyst Cu 16 / Zr / SiO2 and XRD patterns of the samples after reaction. Cu 16 In addition to the characteristic peaks of amorphous SiO2, the / Zr / SiO2 sample also contains characteristic peaks of CuO PDF#45-0937 and ZrO2 PDF#50-1089. 16 In addition to the characteristic peaks of amorphous SiO2, the sample after the reaction of / Zr / SiO2 also contains characteristic peaks of Cu PDF#04-0836 and ZrO2 PDF#50-1089. Figure 1 In comparison, Cu 16Zr@SiO2 improves the sintering resistance of the catalyst, and no large-sized metal nanoparticles appear, but metal oxide nanoclusters are formed, resulting in Figure 1 There are no characteristic peaks related to Cu and Zr.
[0154] Figure 6 For the traditional supported catalyst Cu 16 H2-TPR diagram of / Zr / SiO2. The peak at 237℃ corresponds to the reduction peak of Cu nanoparticles with weak interaction with SiO2.
[0155] Figure 7 For the traditional supported catalyst Cu 16 TEM image of Cu / Zr / SiO2. 16 / Zr / SiO2 electron microscopy images show the presence of large metal nanoparticles in the catalyst.
[0156] Figure 8 For the traditional supported catalyst Cu 16 / Zr / SiO2 and Cu obtained in Example 5 of the present invention 16 Schematic diagram of anti-sintering of Zr@SiO2. Figure 8 It can be seen that SiO2 coated material Cu 16 After high temperature treatment, the size of the Zr@SiO2 nanoclusters only slightly increased. 16 After high temperature treatment, the size of nanoparticles of / Zr / SiO2 increased significantly, thus agglomerating.
[0157] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A SiO2 coated structural material, characterized in that: It comprises SiO2 nanospheres and metal oxide nanoclusters encapsulated inside the SiO2 nanospheres; the metal elements of the metal oxide nanoclusters include Cu and at least one of Zr, Yb, Hf, Y and Zn; The method for preparing the SiO2 coated structural material comprises the following steps: An alkane organic solvent, a surfactant, ammonia water, an acetylacetonate metal salt and a silicon source are mixed, and hydrolyzed and polycondensed, and solid-liquid separated to obtain a SiO2-coated acetylacetonate metal salt material; the acetylacetonate metal salt comprises copper acetylacetonate, and at least one of zirconium acetylacetonate, ytterbium acetylacetonate, hafnium acetylacetonate, yttrium acetylacetonate and zinc acetylacetonate; the silicon source comprises tetramethoxysilane and octadecyltrimethoxysilane; The SiO2 coated acetylacetonate metal salt material is calcined to obtain the SiO2 coated structural material.
2. The SiO2 coated structural material according to claim 1, characterized in that: The diameter of the SiO2 nanospheres is 20-30 nm.
3. The SiO2 coated structural material according to claim 1 or 2, characterized in that: The molar ratio of the metal oxide nanoclusters to SiO2 is (0-2.18):(3.29-52.23), and the molar number of the metal oxide nanoclusters is not zero.
4. The method for preparing the SiO2 coated structural material according to any one of claims 1 to 3, characterized in that: The following steps are involved: An alkane organic solvent, a surfactant, ammonia water, an acetylacetonate metal salt and a silicon source are mixed, and hydrolyzed and polycondensed, and solid-liquid separated to obtain a SiO2-coated acetylacetonate metal salt material; the acetylacetonate metal salt comprises copper acetylacetonate, and at least one of zirconium acetylacetonate, ytterbium acetylacetonate, hafnium acetylacetonate, yttrium acetylacetonate and zinc acetylacetonate; the silicon source comprises tetramethoxysilane and octadecyltrimethoxysilane; The SiO2 coated acetylacetonate metal salt material is calcined to obtain the SiO2 coated structural material.
5. The preparation method according to claim 4, characterized in that: The molar ratio of the copper acetylacetonate to the metal salt of acetylacetonate other than copper acetylacetonate is (0-0.9):(0-1.28), and both are not 0.
6. The preparation method according to claim 4 or 5, characterized in that: The molar ratio of the acetylacetonate metal salt to the silicon source is (0-2.18):(3.29-52.23), and the acetylacetonate metal salt is not zero.
7. The preparation method according to claim 4, characterized in that: The calcination temperature is 600-800° C., and the heat preservation time is 2-6 hours.
8. The preparation method according to claim 4, characterized in that: The calcination atmosphere is air atmosphere.
9. Use of the SiO2 coated structural material according to any one of claims 1 to 3 or the SiO2 coated structural material prepared by the preparation method according to any one of claims 4 to 8 as a catalyst in catalyzing the one-step process of ethanol to butene.
Citation Information
Patent Citations
Metallic nano cluster / silicon dioxide hollow nuclear shell structured nanoparticles and preparation method thereof
CN102019431A
Cu-Zr / SiO2 catalyst, preparation method thereof and application of Cu-Zr / SiO2 catalyst in one-step preparation of butadiene from ethanol
CN116196924A